Studi Netnografi pada WhatsApp Group Komunitas Walk The Street Medan tentang Street Photography - Erwin Surya; Agung Suharyanto; Rehia K. Isabela Barus (Jurnal Antropologi Sumatera, 2023)
The research purposes to see the netnography that occurs in the WTSM community in WAG about street photography. In this research, researchers used a virtual ethnographic approach. Virtual ethnography is an ethnographic method used to observe social phenomena and or user culture in cyberspace. Communication in the WAG Community WTSM is a social interaction that occurs in an open, flexible, and dynamic way. Every day WTSM Community members interact with each other, discuss with each other. This makes the knowledge of WTSM Community members grow, especially in the field of street photography. The social integration that occurs in the WTSM Community WAG can be seen from the social activities carried out by fellow members, these mutual help activities build good integration among members. Based on the contents of the WAG conversation, the WTSM Community has a star pattern communication pattern, each member communicates with each other without any relationship restrictions between members, so that each member is free to communicate with all members.